Kryminalizacja finansowania terroryzmu w świetle przepisu art. 165a kodeksu karnego : część 1 - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Progressing globalization, ease of movement and the pace of information flow undoubtedly have intensified the threat of an important social problem — terrorism. An key instrument of combating terrorist activity is counteracting its financing. This article will analyze the crime of financing terrorism, which has been typified in Art. 165a of the Polish Criminal Code. An attempt will be made to answer the question of whether the legislative measures taken in the above-mentioned scope are purposeful, necessary and justified. The genesis of the current legal regulations in the field of counteracting the financing of terrorism in the Polish penal code will be also presented.
Keywords: terroryzm; finansowanie terroryzmu; akt terrorystyczny; działalność terrorystyczna; przestępczość grupowa